Birth Experience Satisfaction Among Birth Plan Mothers [5]. (May 2015) - Mei, Jenny Y.; Afshar, Yalda R.; Wong, Melissa; Gregory, Kimberly D.; Kilpatrick, Sarah J.; Esakoff, Tania F.
Abstract : INTRODUCTION: Birth plans aim to enable mothers to make informed decisions regarding their deliveries. Our study analyzed birth plans, evaluated the breadth of individual requests, and correlated requests with patient satisfaction. METHODS: This is a prospective controlled trial of singleton pregnancies with and without birth plans. Pre-written birth plans and post-delivery patient surveys were collected evaluating overall satisfaction, expectations, and sense of control. Differences between groups were analyzed using chi-square, linear regression, and Spearman rank correlation. RESULTS: Three hundred two women met criteria —145 had a birth plan and 109 birth plans were collected. We established 23 common requests. The most common requests were: no intravenous medications (82%), exclusive breastfeeding (74%), and no epidural (73%). The requests most fulfilled were avoidance of episiotomy (100%), erythromycin (82%), and rupture of membranes (79%). The highest odds ratios (OR) were for avoidance of erythromycin (OR 57.5; CI: 16.06–205.87), vitamin K (OR 18.6; CI: 3.02–114.61) and epidural (OR 3.01; CI 0.95–9.55). A greater number of requests correlated with meeting expectations less ( P =.04) and feeling less in control ( P =.04). Having a higher percentage of requests met correlated with having expectations met more ( P =.03) and feeling more in control ( P =.03). CONCLUSION: Birth plans demonstrate an array of requests and varied fulfillment. Greater requests correlate with a negative birth experience, whereas having more requests fulfilled correlates with a positive experience. Further research is needed to understand how to improve childbirth-related patient satisfaction and birth experience.